CORPORATE REGULATION DEVELOPMENT COMPANY PT. LIMSONINDO KUNDUR MANDIRI - Winda Fitri; Darwin Darwin (ConCEPt - Conference on Community Engagement Project, 2022)
In a country, labor occupies a fairly important place because it is a matter that affects the material and cultural progress of the country itself. So it must have the best arrangements to overcome various employment problems, one of which is the right of workers to support decent work and livelihoods. In Law No. 13 of 2003 concerning Manpower, it regulates matters relating to worker protection, including the right to fair wages, leave rights, social security, employee relations (Employment Contract). The reform of labor laws and regulations aims to provide justice and protection for workers, as well as to fulfill the mission of the 1945 Constitution, namely the achievement of development and social development of the Indonesian people as a whole. This Community Service uses the Advocacy method in assisting partners (employers) in making their legal documents. The result achieved in this Community Service is the draft of a new Company Regulation.